Interpersonal entrainment in Indian instrumental music performance: Synchronization and movement coordination relate to tempo, dynamics, metrical and cadential structure. (September 2019) - Clayton, Martin; Jakubowski, Kelly; Eerola, Tuomas
Two complementary aspects of interpersonal entrainment – synchronization and movement coordination – are explored in North Indian classical instrumental music, in the auditory and visual domains respectively. Sensorimotor synchronization (SMS) is explored by analysing pairwise asynchronies between the event onsets of instrumental soloists and their tabla accompanists, and the variability of asynchrony by factors including tempo, dynamic level and metrical position is explored. Movement coordination is quantified using cross wavelet transform (CWT) analysis of upper body movement data, and differences in CWT Energy are investigated in relation to the metrical and cadential structures of the music. The analysis demonstrates that SMS within this corpus varies significantly with tempo, event density, peak levels and leadership. Effects of metrical position on pairwise asynchrony are small and offer little support for the hypothesis of lower variability in synchronization on strong metrical positions; a larger difference was found at cadential downbeats, which show increased melody lead. Movement coordination is greater at metrical boundaries than elsewhere, and most strikingly is greater at cadential than at other metrical downbeats. The implications of these findings for understanding performer coordination are discussed in relation to ethnographic research on the genre.